2011
DOI: 10.1038/tpj.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of the rs4149056 variant in SLCO1B1 on myopathy associated with simvastatin and atorvastatin

Abstract: Statins reduce cardiovascular morbidity and mortality in appropriately selected patients. However, statin-associated myopathy is a significant risk associated with these agents. Recently, variation in the SLCO1B1 gene was reported to predict simvastatin-associated myopathy. The aim of this study was to replicate association of the rs4149056 variant in SLCO1B1 with severe statin-associated myopathy in a cohort of patients using a variety of statin medications and to investigate the association with specific sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 21 publications
10
133
1
3
Order By: Relevance
“…Similarly, Fu et al [31] reported no significant effect on atorvastatin efficacy in a Chinese population. In agreement with this are findings showing that genetic variants of OATP1B1 are not predictive for atorvastatin-associated myopathic side effects [15]. It should be noted at this point that in healthy volunteers, the OATP1B1 polymorphisms exerted a more pronounced effect on pharmacokinetic parameters of the atorvastatin acid levels compared with the less lipophilic rosuvastatin [32].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similarly, Fu et al [31] reported no significant effect on atorvastatin efficacy in a Chinese population. In agreement with this are findings showing that genetic variants of OATP1B1 are not predictive for atorvastatin-associated myopathic side effects [15]. It should be noted at this point that in healthy volunteers, the OATP1B1 polymorphisms exerted a more pronounced effect on pharmacokinetic parameters of the atorvastatin acid levels compared with the less lipophilic rosuvastatin [32].…”
Section: Discussionsupporting
confidence: 58%
“…In particular, the frequent single nucleotide polymorphism (SNP) SLCO1B1 c.521C results in significant changes in pharmacokinetics (increased area under the curve) of several statins (pravastatin, atorvastatin, rosuvastatin and simvastatin) in healthy volunteers (summarized in the study of Niemi et al [13]). The assumption that OATP1B transporters are important in pharmacokinetics of statins is indirectly supported by findings showing that the frequently occurring functionimpairing allele SLCO1B1 c.521C is most predictive for extrahepatic adverse events (myopathy, rhabdomyolysis) of simvastatin therapy [14,15]. In detail, Link and colleagues had identified the noncoding rs4363657 polymorphism after performing a Genome-wide association scan in patients experiencing simvastatin-induced myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The association was replicated in patients on 40 mg of simvastatin and has subsequently also been replicated by other investigators [25]. Although this association seems to be important for simvastatin-induced myopathy, whether it is also important for the other statins still requires further study [26]. As with GWAS in complex diseases, a finding that might not show clinical value might still be of use in identifying the mechanism(s) of action of the drug [27 ‱ , 28 ‱ , 29 ‱ ].…”
Section: Cep68mentioning
confidence: 59%
“…68 It was statemented that plasma statin concentration liable to be higher in people with the above polymorphism, in consequence predisposing them to adverse effects. 67,69 On the other hand, modern studies have shown that this polymorphism might be largely associated with simvastatininduced myopathy. 70 It was identified by SEARCH collaborative group that rs4149056 polymorphism of SLCO1B1 (521C variant) was associated with a 4.5 fold increased risk of myopathy in heterozygotes and 17 fold higher risk in homozygotes when co administered with simvastatin 80 mg daily.…”
Section: Polymorphismmentioning
confidence: 99%